2003
DOI: 10.1038/sj.eye.6700377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fibrovascular traction and pooling of tears on corneal topographic changes induced by pterygium

Abstract: Aim To investigate the effects of fibrovascular traction and the pooling of tears at the pterygium apex on the corneal topographic changes induced by pterygium. Methods A total of 16 eyes of 14 cases with primary pterygium were included in the study. A computerized corneal topography system was used for corneal topography examinations. Baseline keratographs were taken two times at straight gaze. A repeat corneoscope photograph was immediately obtained in temporal gaze. Then the tears at the pterygium apex were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
3
25
0
2
Order By: Relevance
“…Pterygium-induced corneal flattening and its topographic changes have been attributed to the pooling of tears at the pterygium apex or to the mechanical traction by the pterygium fibrovascular tissue [1,30]. A recent study by Yasar et al emphasized the role of tear pooling by ruling out the effects of mechanical traction [31]. However, changes in the back corneal surface, as observed in our study, reveal that at least some of the pterygium-induced topographic changes are due to alterations in the corneal shape which are reversed after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pterygium-induced corneal flattening and its topographic changes have been attributed to the pooling of tears at the pterygium apex or to the mechanical traction by the pterygium fibrovascular tissue [1,30]. A recent study by Yasar et al emphasized the role of tear pooling by ruling out the effects of mechanical traction [31]. However, changes in the back corneal surface, as observed in our study, reveal that at least some of the pterygium-induced topographic changes are due to alterations in the corneal shape which are reversed after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For tear dynamics, a recent study has shown that there is a pooling of tears at the pterygium apex as evidenced by the significantly increased total corneal refractive power after the tears were dried. 22 The pooling of tears, presumably caused by the protrusion of pterygial lesion, can disturb the distribution of tear film on the ocular surface. It is still unclear whether the tear volume plays a role in the abnormal tear function in pterygia patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, fibrovascular traction was the cause of structural and topographic corneal changes even though the pooling of tears at the pterygium head is known to play an important role on corneal topography in most cases. 7 Even though preoperative automated keratometry showed a high with-the-rule astigmatism on the right side, the patient's subjective refraction was spherical. It is known, however, that the induced irregular astigmatism caused by pterygia is not always apparent by subjective refraction.…”
Section: Commentmentioning
confidence: 90%